Formal Synthesis of Corynanthe Indole Alkaloid (±)-Mitralactonine: Construction of α-Hydroxy-Keto Functionalized Tetracyclic Skeleton - Dumare, Nilesh B.; Sharma, Pallavi; Sivappa, Rasapalli; Chavan, Subhash P. (Chemistryselect, 2025)
An efficient synthesis of a tetracyclic skeleton common to many corynanthe alkaloids was accomplished in 10 linear steps starting from a known tetrahydro beta-carboline intermediate. The tetracyclic alpha-hydroxy keto functionalized advanced precursor of (+/-)-mitralactonine was realized using Wittig olefination, ketohydroxylation of a trisubstituted alkene, and a tandem amine unmasking-intramolecular nucleophilic displacement reaction for C-N bond formation of C/D-rings.
Keywords: alpha-hydroxy keto; beta-carboline; corynanthe alkaloid; intramolecular N-alkylation; mitragynine